Keynote address by eco-technology senior lecturer at International Conference on Agricultural Technology and Engineering, and Environmental Sciences (ICATES) 2021 - UiTM, Faculty of Applied Sciences (Faculty of Applied Sciences, 2021)
Faculty of Applied Sciences (FSG), UiTM Shah Alam delivered a keynote speech entitled ‘Bamboo, a Great Plant for Green Plan’. The speech provides information on bamboo research accomplishments that are very useful in promoting the potentials of bamboo as a great raw material for global green development and consumption planning.